Sport brand ambassadors' experiences in sponsored user-generated branding programs. Issue 4 (1st June 2020) - Geurin, Andrea N.
Abstract : Purpose: The purpose of this study was to develop an initial understanding of sport brand ambassador participants' experiences in sponsored user generated branding (UGB) programs to assist sport organizations in developing the most mutually beneficial brand ambassador programs possible. Design/methodology/approach: Semi-structured interviews were held with six individuals who serve as brand ambassadors for various sport brands. Data were analyzed using qualitative thematic analysis. Findings: Participants were intrinsically motivated to serve in brand ambassador roles. Their experiences were impacted by whether their personal expectations were met, perceived relationship with the brand, perceived value to the brand, and perceived amount of work involved. They reported the best aspects of participation were a sense of community and free products and/or discounts. The most challenging aspects included not wanting to come across as a marketer, self-inflicted pressure to perform a certain way for the brand, pressure to purchase products, and lack of clear communication from the brand. Research limitations/implications: As this study was qualitative, the findings are unique to the participants and the brands they represent. Therefore, the findings may be used to guide other research and brands but are not generalizable. Practical implications: Sport brands wishing to employ sponsored UGB strategies such as brand ambassador programs must set clear expectations for ambassadors, communicate regularly, and develop a sense of community with and among ambassadors. Originality/value: This study contributes to the limited sport management research on sponsored UGB and offers theoretical and practical implications in the areas of sport marketing and branding.